2018
DOI: 10.1097/mph.0000000000001144
|View full text |Cite
|
Sign up to set email alerts
|

Triptorelin for Fertility Preservation in Adolescents Treated With Chemotherapy for Cancer

Abstract: Our study suggests that gonadotropin releasing hormone-a administered during chemotherapy can prevent premature ovarian failure in patients treated without HSCT and that it is not enough to preserve the ovarian function during HSCT. Hence, a prospective randomized trial with a larger population would be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
0
10
0
1
Order By: Relevance
“…High LH dosage could adversely alter factors required for fertility, as previously described ( Flaws et al , 1997 ), and reported for some drugs ( Bertoldo et al , 2020 ; Park et al , 2020 ). Administering gonadotropin-releasing hormone agonists (GnRHa) during chemotherapy can improve reproductive outcomes in oncologic patients ( Blumenfeld et al , 2015 ; Meli et al , 2018 ; Sinha et al , 2018 ), but their efficacy as gonadoprotective agents is controversial ( Bildik et al , 2015 ; Horicks et al , 2018 ; Lambertini et al , 2018 ; Sofiyeva et al , 2019 ). The effects induced by our proposed LH treatment and the GnRHa therapies currently in use mainly differ in terms of treatment duration and cumulative dosage.…”
Section: Discussionmentioning
confidence: 99%
“…High LH dosage could adversely alter factors required for fertility, as previously described ( Flaws et al , 1997 ), and reported for some drugs ( Bertoldo et al , 2020 ; Park et al , 2020 ). Administering gonadotropin-releasing hormone agonists (GnRHa) during chemotherapy can improve reproductive outcomes in oncologic patients ( Blumenfeld et al , 2015 ; Meli et al , 2018 ; Sinha et al , 2018 ), but their efficacy as gonadoprotective agents is controversial ( Bildik et al , 2015 ; Horicks et al , 2018 ; Lambertini et al , 2018 ; Sofiyeva et al , 2019 ). The effects induced by our proposed LH treatment and the GnRHa therapies currently in use mainly differ in terms of treatment duration and cumulative dosage.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that GnRHa co-treatment may significantly decrease the POF rate from 82–33% in patients with lymphomas. Moreover, a recent single-center retrospective study on postmenarchal adolescent patients (median age 14, range 11 to 18) showed that GnRHa preserved ovarian function and fertility in adolescents treated for acute lymphoblastic leukemia, acute myeloid leukemia, Hodgkin lymphoma, or other cancers ( 100 ). On the last clinical visit, 29 patients (81%) had a regular menstrual cycle, three (8%) oligomenorrhea, and four (11%) amenorrhea.…”
Section: The Clinical Perspective: Concluded and Ongoing Trialsmentioning
confidence: 99%
“…Ovarian suppression with gonadotropin releasing hormone (GnRH) analogs —Numerous trials and meta-analyses have demonstrated a correlation between the use of GnRH analogs before and during chemotherapy treatment and lower incidence of premature ovarian insufficiency in young girls facing cancer [ 64 , 65 , 66 , 67 , 68 , 69 ] GnRH indirectly suppresses ovarian function by suppressing gonadotropin secretion from the pituitary gland [ 70 , 71 ]. The use of GnRH analogs in most cases does not protect against gonadotoxic effects of radiotherapy, especially if treatments associated with a high risk of gonadotoxicity are used such as preparation for hematopoietic stem cell transplantation [ 43 , 69 ]. Their usage in fertility preservation is still debatable.…”
Section: Fertility Preservation Methodsmentioning
confidence: 99%